Consumer behavior: analysis of factors influencing in the pet segment (Revista Brasileira de Contabilidade e Gestão, 2020)
When considering the importance of history as a learning tool for future actions, combined with the temporal sequences that explain economic and social development, this research has set itself the objective of identifying the trajectory of the açaí entrepreneur when it is studied from the conceptual perspective of dependence on Trajectory. Through a predominantly bibliographic research method, it was concluded that the entrepreneur who today acts as an açaí beater in the cities of the Brazilian Amazon had as a precursor the man who worked in guilds in the free cities of Europe, permeated the historical performance of the black and of the Indian in the Brazilian Amazon and culminated with the Northeastern who, after the decline of the golden age of rubber, began to extractivism in the holes and rivers that surround the cities of the Brazilian Amazon. In summary, this was the trajectory dependency of today's açaí entrepreneur who operates in the cities of the Brazilian Amazon.
Keywords: Acai Berry Whisk; Trajectory Dependency; Golden Era of Rubber; Brazilian Amazon